Stress resilience : molecular and behavioral aspects - Chen, Alon (Academic Press, 2020)
This book presents the first reference available on the full-breadth of cutting-edge research being carried out in this field. It includes a wide range of basic molecular knowledge on the potential associations between resilience phenomenon and biochemical balance, but also focuses on the molecular and cellular mechanisms underlying stress resilience. World-renowned experts provide chapters that cover everything from the neural circuits of resilience, the effects of early-life adversity, and the transgenerational inheritance of resilience. This is a resource for neuroscientists and biological psychiatrists who want to improve their understanding of the consequences of stress and on how some people are able to avoid it. It approaches resilience as a process rather than as a static trait; Provides basic molecular knowledge on the potential associations between resilience phenomenon and biochemical balance; Presents thorough coverage of both the genetic and environmental factors that contribute to resilience.